2015
DOI: 10.1136/bmj.h1019
|View full text |Cite
|
Sign up to set email alerts
|

The impact of providing rapid diagnostic malaria tests on fever management in the private retail sector in Ghana: a cluster randomized trial

Abstract: Objective To examine the impact of providing rapid diagnostic tests for malaria on fever management in private drug retail shops where most poor rural people with fever present, with the aim of reducing current massive overdiagnosis and overtreatment of malaria.Design Cluster randomized trial of 24 clusters of shops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(149 citation statements)
references
References 54 publications
6
117
0
Order By: Relevance
“…Studies in settings where antibiotics are not available to prescribers, such as chemist shops in Ghana, have shown that withholding both antibiotics and antimalarials diverts patients to antipyretics, which is a safe strategy for most uncomplicated illness. 57 With declining incidence of malaria in many settings, the proportion of fevers attributable to illnesses other than malaria stands to increase. Currently rapid diagnostic tests are more useful to rule out malaria than to rule it in, at least in Africa, but this is likely to change as the incidence of malaria drops.…”
Section: Strengths and Weaknesses Of Studymentioning
confidence: 99%
“…Studies in settings where antibiotics are not available to prescribers, such as chemist shops in Ghana, have shown that withholding both antibiotics and antimalarials diverts patients to antipyretics, which is a safe strategy for most uncomplicated illness. 57 With declining incidence of malaria in many settings, the proportion of fevers attributable to illnesses other than malaria stands to increase. Currently rapid diagnostic tests are more useful to rule out malaria than to rule it in, at least in Africa, but this is likely to change as the incidence of malaria drops.…”
Section: Strengths and Weaknesses Of Studymentioning
confidence: 99%
“…In sub-Saharan Africa, most cases of uncomplicated malaria are treated presumptively on the basis of symptoms rather than a positive test or formal medical diagnosis, and treatment medication is purchased from a local store or pharmacy ( 30 ). Because of this, we conservatively assumed that disruption of health services from the Ebola outbreak only affected treatment for severe malaria.…”
Section: Methodsmentioning
confidence: 99%
“…12 Most of the population lives in scattered small communities of less than 2000 people. Vehicular transport is unavailable in many parts of the district and people have to walk long distances (approx.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 56 chemical sellers and 6 pharmacies also sell pharmaceutical products and their diagnostic practice is described elsewhere. 12 Chemical sellers are regulated by law and supervised by the Pharmacy Council, which also regulates pharmacies. To be eligible to apply for a chemical seller's license, a person must possess a minimum qualification of General Certificate of Examination (GCE) Ordinary Level Certificate or a Senior Secondary School (SSS) Certificate with basic knowledge in healthcare delivery being an advantage.…”
Section: Methodsmentioning
confidence: 99%